Architecture of Independent Learning: A Study of Teacher Competencies in Designing Contextual Teaching Modules in Elementary Schools - Sisra Maiyola Sari; Dela Silvani (Institution of Scientific Publishing and Publication of the Yayasan Dzaky Elmumtaz Qurani, 2026)
This study aims to analyze the competency of elementary school teachers in designing instruction aligned with the implementation of the Kurikulum Merdeka (Independent Curriculum). This curriculum necessitates a shift in the pedagogical paradigm, requiring teachers to possess high pedagogical, professional, and creative competencies to foster student-centered learning environments. Methods: A descriptive qualitative method was employed. Data were gathered through observations of instructional materials, in-depth interviews with teachers, and documentary studies of teaching modules and diagnostic assessment instruments. Results: The findings reveal that teachers have acquired a fundamental understanding of the Kurikulum Merdeka concepts, such as Learning Outcomes (Capaian Pembelajaran) and the Pancasila Student Profile, and are capable of developing teaching modules independently. However, the implementation of differentiated learning and the utilization of formative assessments remain suboptimal. Furthermore, there is a significant variation in teachers' instructional technology literacy, which directly impacts the quality of instructional design. Conclusion: This research concludes that teacher competency in instructional design is currently in a transitional phase and requires reinforcement through continuous training and practical professional mentoring. The successful implementation of the Kurikulum Merdeka fundamentally depends on the comprehensive improvement of teacher competencies